Modeling the Impact of Excipients Selection on Nitrosamine Formation towards Risk Mitigation - Alberto Berardi; Maarten Jaspers; Bastiaan H. J. Dickhoff (MDPI AG, 2023)
Risk control for nitrosamine impurities in drug products is currently a major challenge in the industry. Nitrosamines can form during drug product manufacturing and storage through the reaction of nitrites with amine-containing APIs or impurities. The level of nitrites in excipients and the rate of reaction often control the build-up of nitrosamine. Although the variability in nitrite levels across excipient types and suppliers is well recognized, the impact of excipient selection on the level of nitrosamine formed has not been systematically studied. This gap of knowledge is addressed in the current work. We present theoretical case studies of formulations where microcrystalline cellulose (MCC), or lactose supplier, or superdisintegrant type are changed in pursuit of lower levels of nitrite. The impact of the average, maximum, and minimum levels of nitrites in each excipient on nitrosamine formation in the dosage form is calculated. The input data for this calculation are the formulation composition, nitrosamine molecular weight (MW), percentage of conversion, and nitrite levels per excipient. The percentage of conversion (based on the formulation and manufacturing variables) and nitrite levels were taken from the recent literature. We show that changing the supplier of a single excipient, or of the three most critical excipients, can reduce nitrosamine formation by up to −59% and −89%, respectively. We also show that high-risk formulations, e.g., high MW nitrosamines, high dosage weights, and high percentages of conversion (e.g., wet granulation), can often be de-risked below regulatory acceptable daily intake via careful excipient selection. Finally, we provide an open-access tool that enables users to calculate the theoretical formation of nitrosamines in their specific formulations. This calculation template can be used for (i) the preliminary screening of the risk of nitrosamine formation in drug products and (ii) the preliminary assessment of the impact of excipient selection for risk mitigation.